2021
DOI: 10.1093/mnras/stab623
|View full text |Cite
|
Sign up to set email alerts
|

Hard X-ray selected giant radio galaxies – III. The LOFAR view

Abstract: Giant radio galaxies (GRGs), with extended structures reaching hundreds of kpc, are among the most spectacular examples of ejection of relativistic plasma from supermassive black holes. In this work, third of a series, we present LOw Frequency ARray (LOFAR) images at 144 MHz, collected in the framework of the LOFAR Two-metre Sky Survey Data Release 2 (LoTSS DR2), for nine sources extracted from our sample of hard X-ray selected GRGs (HXGRG, i.e. from INTEGRAL/IBIS and Swift/BAT catalogues at >20 keV). T… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 87 publications
(154 reference statements)
4
9
0
Order By: Relevance
“…The present study showcases the fact that the jet precession model is capable of producing the morphology typically observed in winged sources, whose formation scenario is long being debated (Rottmann 2002;Gopal-Krishna et al 2012;Giri et al 2022). However, further studies are required in order to confirm this model's universality by extending it to larger scaled winged sources, as is typically found in observations (see Capetti et al 2002;Bruni et al 2021). We also note here that our simulations are not designed to resolve the origin of jet precession that is causing the winged structure to form.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…The present study showcases the fact that the jet precession model is capable of producing the morphology typically observed in winged sources, whose formation scenario is long being debated (Rottmann 2002;Gopal-Krishna et al 2012;Giri et al 2022). However, further studies are required in order to confirm this model's universality by extending it to larger scaled winged sources, as is typically found in observations (see Capetti et al 2002;Bruni et al 2021). We also note here that our simulations are not designed to resolve the origin of jet precession that is causing the winged structure to form.…”
Section: Discussionsupporting
confidence: 68%
“…• Spectral properties and polarization: The fact that the observed winged morphology of 2MASX J1203 can form based on a precessing jet's evolution in a galactic environment is clearly supported by our synthetic emission maps. A large scale analogy of this structure has recently been reported by Bruni et al (2021) who have alluded its formation mechanism to a precessing jet as well. These sources are a strong contender for hosting a binary super massive black hole system at their core which would necessitate further high resolution observations to detect them, hence resolving their formation scenarios.…”
Section: Discussionmentioning
confidence: 54%
“…Recent evidence for the Back-flow model is provided by Cotton et al (2020), where they show a double-boomerang structure supporting the findings of Leahy & Williams (1984) and comparable to the results of numerical simulations by Rossi et al (2017). The role of an over-pressured cocoon in forming a giant radio galaxy with X-shaped morphology is also shown recently by Bruni et al (2021).…”
Section: Introductionsupporting
confidence: 79%
“…An asymmetry in wing formation, that is the bending of back-flowing materials before reaching centre can be seen in the y-x plane i.e. when viewed along the z-axis of the galaxy, where a similar bending of back-flowing plasma has also been observed in several XRGs (Cotton et al 2020;Bruni et al 2021). However, our structure is still in its initial stage of formation (3.91 Myr) and in this regard, it would be interesting to further follow its long term evolution.…”
Section: Jet At An Angle To the Major Axismentioning
confidence: 74%
“…Finally, we have shown that the large-scale environment of J1430 is not underdense with respect to other 50 random galaxies at the same redshift. All these pieces of evidence seem to suggest that J1430 is rather old and evolved, although with no clear sign of recent restarting of its nuclear activity, unlike what has been shown and found for hard X-ray selected GRGs with deep LOFAR imaging (e.g., Bruni et al 2021). When compared with the whole GRG population of the SAGAN sample (Dabhade et al 2020b), J1430 is among the highest redshift GRGs known to date, and the highest redshift GRG in the SAGAN sample with a radio spectral index between 150 MHz and 1.4 GHz α < −1.…”
Section: Discussionmentioning
confidence: 76%